A review of NEST models for liquid xenon and an exhaustive comparison with other approaches - Szydagis, M.; Balajthy, J.; Block, G. A.; Brodsky, J. P.; Brown, E.; Cutter, J. E.; Farrell, S. J.; Huang, J.; Kamaha, A. C.; Kozlova, E. S.; Liebenthal, C. S.; McKinsey, D. N.; et al. (Frontiers in Detector Science and Technology, 2025)
This paper discusses the microphysical simulation of interactions in liquid xenon, the active detector medium in many leading rare-event searches for new physics, and describes experimental observables useful for understanding detector performance. The scintillation and ionization yield distributions for signal and background are presented using the Noble Element Simulation Technique (NEST), a toolkit based on experimental data and simple empirical formulas, which mimic previous microphysics modeling but are guided by data. The NEST models for light and charge production as a function of the particle type, energy, and electric field are reviewed, along with models for energy resolution and final pulse areas. NEST is compared with other models or sets of models and validated against real data, with several specific examples drawn from XENON, ZEPLIN, LUX, LZ, PandaX, and table-top experiments used for calibrations.